PERILAKU PENGELOLAAN SAMPAH MEDIS PADAT DI RUMAH SAKIT UMUM LABUANG BAJI KOTA MAKASSAR - Asrijun Juhanto; Hadijah Hadijah; Andi Yusuf (UNM Environmental Journals, 2022)
Medical waste is a type of hazardous waste because it comes from equipment that has the potential to contain infectious agents, toxic and radioactive materials. Many studies suggest that every individual who is involved or interacts with the hospital environment is very vulnerable to exposure to medical waste. Quantitative research method with a cross-sectinal study approach with a total sample of 31 cleaning staff at Laburan Baji Hospital, Makassar City. Data collection was distributed to respondents who were on duty at the time of the study. The results showed that the knowledge of respondents was significantly related to solid medical waste management ρ=0.000 < α=0.05. Respondents' attitudes are significantly related to medical waste management with a value of ρ=0.001 < α=0.05. Respondents' actions were significantly related to solid medical waste management with a value of ρ=0.011<α=0.05. Respondent's skills are not significantly related to solid medical waste management with a value of ρ=0.083> α=0.05. Provision of PPE for respondents was not significantly related to solid medical waste management with a value of ρ=0.074 > α=0.05. The most influential variable is the knowledge of the respondents with Exp(B) value of 57.679. It is expected that cleaning staff will always comply with the rules that have been given to cleaning workers so that they can avoid incidents of being contaminated with medical waste in hospitals.